It's not about the coffee : leadership principles from a life at Starbucks - Behar, Howard (Portfolio, 2007)
During his years as a senior executive at Starbucks, Behar helped establish the Starbucks culture, which stresses the importance of people over profits. Now he reveals the ten principles that guided his leadership--and not one of them is about coffee.--From publisher description.